ALTERNATIF ARANG AKTIF SEBAGAI SOIL CONDITIONING PADA TANAMAN - Gusmailina Gusmailina; Gustan Pari; Sri Komarayati; Tati Rostiwati (Pusat Penelitian dan Pengembangan Hasil Hutan, 2001)
This paper deals with experimental results of utilizing activated charcoal of bamboo and candle nut as a plan 'ts soil conditioning. In this regard the plant species for the experiment was Eucalyptus urophylla with respect to the growth of its seedlings. Further, this experiment was intended to evaluate the effect of activated charcoal to as added to the media of Eucalyptus urophylla seedlings on their growth, and to asses the role of activated charcoal in improving soilfertility.The media for the seedling growth consisted of top soil mixed with activated charcoal of either bamboo or candlenut, compost, and mycorrhiza. The mixture was manipulated into various compo sition and further regarded as a treatment. The media consisting of only topsoil was also used as a control.The parameters as observed were number of leaves, increase in height of Eucalyptus urophylla seedlings, weight and dry weight ofplant, weight of root portion infected by mycorrhiza, and weight ratio of the top to root portion of the plant (T/R ratio). Further, the analyses of nutrients in the media consisted of N, P, K, Ca, and Mg contents before and after experiment.Result showed that the media containing activated charcoal of bamboo are more preferable than that of candlenut, this is because the former media could stimulate the increase in the height of plant seedlings by 27 percent, enhance the additional number of leaves by 29, increase the T/R ratio by 28 percent, and provide better mycorrhyzza growth than the latter media (i.e. containing activated charcoal of candlenut). Further, when the media containing top soil and activated charcoal of bamboo were added with compost, it could stimulate the growth in 4.8 times as much as height of E. urophylla plant.